Aktivitas Antibakteri: Pinostrobin dan Fraksi n-Heksana Rimpang Temu Kunci (Boesenbergia pandurata) terhadap Bakteri Staphylococcus aureus - Anita Puspa Widiyana; Citra Destya Rahma Putri; Rio Risandiansyah Risandiansyah (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
Staphylococcus aureus is a gram-positive bacterium caused by serious infections, and its resistance to antibiotics continues to increase. The rhizome of Boesenbergia pandurata is known to contain terpenylated flavonoids that have potential as new antibacterial agents. This study aimed to isolate the compound pinostrobin from fingerroot, characterize its structure, and evaluate the antibacterial activity of pinostrobin and the n-hexane fraction against S. aureus. The research method included maceration of the fingerroot with ethanol, liquid-liquid fractionation with n-hexane:ethanol (1:1), and purification of pinostrobin by recrystallization. The concentrated extract obtained was 5.51 g (5.5%), and the n-hexane fraction was 0.24 g (4.4%). Structural analysis with FTIR, ¹H-NMR, ¹³C-NMR, and MS confirmed the isolate as pinostrobin. The antibacterial assay by disc diffusion method showed that pinostrobin had zero activity, while the n-hexane fraction produced inhibition zones of 7.5–10.0 mm in the range of 2,500–20,000 ppm. It is concluded that pinostrobin is not active as an antibacterial agent, and the activity of the n-hexane fraction was relatively weak, thus requiring further formulation development to enhance its effectiveness.